Di‐ and Triarylmethylium Ions as Probes for the Ambident Reactivities of Carbanions Derived from 5‐Benzylated Meldrum's Acid. Issue 35 (5th August 2014) - Chen, Xi; Tan, Yue; Berionni, Guillaume; Ofial, Armin R.; Mayr, Herbert
Abstract The kinetics of the reactions of carbocations with carbanions 1 derived from 5‐benzyl‐substituted Meldrum's acids 1‐H (Meldrum's acid=2, 2‐dimethyl‐1, 3‐dioxane‐4, 6‐dione) were investigated by UV/Vis spectroscopic methods. Benzhydryl cations Ar2CH+ added exclusively to C‐5 of the Meldrum's acid moiety. As the second‐order rate constants (kC) of these reactions in DMSO followed the linear free‐energy relationship lg k=sN(N+E), the nucleophile‐specific reactivity parameters N and sN for the carbanions 1 could be determined. In contrast, trityl cations Ar3C+ reacted differently. While tritylium ions of low electrophilicity (E<−2) reacted with 1 through rate‐determining β‐hydride abstraction, more Lewis acidic tritylium ions initially reacted at the carbonyl oxygen of 1 to form trityl enolates, which subsequently reionized and eventually yielded triarylmethanes and 5‐benzylidene Meldrum's acids by hydride transfer.